Pengaruh Media Pembelajaran Geogebra Pada Materi Fungsi Kuadrat Terhadap Motivasi dan Hasil Belajar Peserta Didik - Nur Hamidah; Iis Nur Afidah; Lutfi Wahyu Setyowati; Sutini Sutini; Junaedi Junaedi (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
This study aims to determine the effect of Geogebra learning media on the quadratic function material on motivation and learning outcomes in class IX MTsN Gresik. The method of this research used experimental research mapped in class IX –C and IX-D. Class IX-C as a control class and class IX-D as an experimental class. Where each class there are 28 students. Data collection techniques used were pretest, post-test and questionnaire. Pretest and post-test were used to determine effect of Geogebra on student learning outcomes, while the questionnaire was used to determine the effect of Geogebra on students’ learning motivation. Data analysis uses z-test analysis. The results of the study showed that : (1) Geogebra learning media on quadratic function material influences students’ learning motivation, (2) student learning outcomes using Geogebra learning media on quadratic function material are better than students who do not use Geogebra. Keyword: Geogebra, motivation and learning outcomes, quadratic function.